Kecerdasan Emosional, Kecerdasan Adversitas, Kecerdasan Intelektual, Kecerdasan Spiritual, Perilaku Belajar dan Tingkat Pemahaman Akuntansi - Jelantik, Made Satryawan; Dewi, Luh Gede Krisna (E-Jurnal Akuntansi; Vol 33 No 4 (2023), 2023)
Understanding of accounting is not only aimed at achieving value in the form of numbers, but also understanding of concepts and practical application in society. This study aims to examine the effect of emotional intelligence, adversity intelligence, intellectual intelligence, spiritual intelligence and learning behavior on the level of understanding of accounting. The research was conducted at the Faculty of Economics and Business (FEB) Udayana University, especially the Bachelor of Accounting program. The research population was active 2018 Bachelor of Accounting students at the Faculty of Economics and Business, Udayana University, totaling 238 people. The sample used was 150 respondents who were selected based on the probability sampling technique, namely random sampling. Data collection was carried out using a questionnaire method. The analysis technique used is multiple linear regression analysis. The results showed that the better the emotional intelligence, adversity intelligence, intellectual intelligence, spiritual intelligence and learning behavior of accounting students, the level of understanding of accounting would increase. Keywords: Emotional Intelligence; Adversity Intelligence; Intellectual Intelligence; Spiritual Intelligence; Learning Behavior.